Analisis Semiotik Pada Pelaporan Corporate Social Responsibility (CSR) Saat Pandemi Covid-19 Di Pertamina TBBM Baubau - Endang Tri Pratiwi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Buton, 2021)
The Indonesian Government's efforts in dealing with the Covid-19 outbreak require support from private sector/other institutions with adequate funding capacity. One of the BUMNs that actively contributed to the handling of the outbreak was PT. Pertamina. This study aims to determine the semiotic analysis of Corporate Social Responsibility (CSR) reporting during the Covid-19 pandemic at Pertamina TBBM Baubau. The population were all of Pertamina TBBM Baubau CSR reports, while the sample was Pertamina TBBM Baubau CSR reporting during the Covid-19 pandemic in 2020. Data collection methods were through interviews, documentation, and literature study. The data analysis used is semiotic analysis through a descriptive analytic approach in accordance with the meaning of symbols, words and sentences in the sustainability reporting of Pertamina TBBM Baubau. The results showed that there were four CSR programs that were fully transferred to the handling of Covid-19 at Baubau City in 2020. This condition is a synergy between the Government and managers for efforts to handle Covid-19 through the distribution of CSR funds.